PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS CONCEPT ATTAINMENT MODEL (CAM) DALAM UPAYA MENINGKATKAN PEMAHAMAN KONSEP PADA MATERI LISTRIK STATIS SISWA KELAS XII SMA (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : Physics material is often considered a difficult material for students to understand. This tendency usually starts from the students own experiences, where they find the fact that physics is a lesson that deals with conceptual problems, understanding concepts, and solving complex problems. The purpose of this research is to develop learning tools in the form Learning Implementation Plan (RPP) and the Students Worksheet (LKPD) and concept understanding test questions in an effort to improve understanding of valid concepts on static electricity material for class 12th high school students. The development of learning tools is carried out as a solution to the lack of understanding of students concepts on static electricity material. The type of used is Research and Development (R&D) used the Plomp development model with a modified phase as needed, starting from the preliminary research, design, and realization or construction. The data collection instruments used were interview guidelines and validation sheets. The result of the validation assesment from the validator were analyzed on each assesment indicator so that the level of validity of each learning tools was obtained. Validation was carried out 2 times, the results of first validation learning tools contained an average asessment score less than 3 in the less category and invalid. Then, the learning tools is repaired according to the suggestions for improvement. The results of the second validation of the learning tools as a whole are in the good category and are declared valid. The average result of second validation RPP as a whole is 3,59, the average result of second validation LKPD as a whole is 3,31 and the second validation result of the concept understanding test gets a score 3,31. So from the assesment scores that have been described, the learning tools based on the concept attainment learning model are valid and suitable for use in the physics learning process.Key Word : Learning Tools, Concept Attainment, Static Electricity